Structure–Function Decoupling: A Novel Perspective for Understanding the Radiation-Induced Brain Injury in Patients With Nasopharyngeal Carcinoma - Kang, Ya-fei; Chen, Rui-ting; Ding, Hao; Li, Li; Gao, Jian-ming; Liu, Li-zhi; Zhang, You-ming (Frontiers in Neuroscience, 2022)
Radiation-induced functional and structural brain alterations are well documented in patients with nasopharyngeal carcinoma (NPC), followed by radiotherapy (RT); however, alterations in structure–function coupling remain largely unknown. Herein, we aimed to assess radiation-induced structure–function decoupling and its importance in predicting radiation encephalopathy (RE). We included 62 patients with NPC (22 patients in the pre-RT cohort, 18 patients in the post-RT-RE+ve cohort, and 22 patients in the post-RT-RE–ve cohort). A metric of regional homogeneity (ReHo)/voxel-based morphometry (VBM) was used to detect radiation-induced structure–function decoupling, which was then used as a feature to construct a predictive model for RE. Compared with the pre-RT group, patients in the post-RT group (which included post-RT-RE+ve and post-RT-RE–ve) showed higher ReHo/VBM coupling values in the substantia nigra (SN), the putamen, and the bilateral thalamus and lower values in the brain stem, the cerebellum, the bilateral medial temporal lobes (MTLs), the bilateral insula, the right precentral and postcentral gyri, the medial prefrontal cortex (MPFC), and the left inferior parietal lobule (IPL). In the post-RT group, negative correlations were observed between maximum dosage of RT (MDRT) to the ipsilateral temporal lobe and ReHo/VBM values in the ipsilateral middle temporal gyrus (MTG). Moreover, structure–function decoupling in the bilateral superior temporal gyrus (STG), the bilateral precentral and postcentral gyri, the paracentral lobules, the right precuneus and IPL, and the right MPFC exhibited excellent predictive performance (accuracy = 88.0%) in identifying patients likely to develop RE. These findings show that ReHo/VBM may be a novel effective imaging metric that reflects the neural mechanism underlying RE in patients with NPC.